Implementation of warm water sponge intervention for the diagnosis of hyperthermia in children with phase I dengue hemorrhagic fever - Puspita Putri Haryuni; Ika Rizki Anggraini (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: The incidence of dengue hemorrhagic fever (DHF) in Indonesia continues to increase annually. Fever is a common problem experienced by DHF patients. Various interventions can be implemented to address this issue, one of which is water warm. Purpose: To determine the effectiveness of applying warm water sponge to dengue hemorrhagic fever patients with hyperthermia. Method: The method used in this case study is descriptive with a nursing care process approach. The subject in this case study was one respondent with inclusion criteria of having hyperthermia or a body temperature > 37˚ C and being of school age. Results: The results obtained according to the development of the graph in 3 days were that there was a decrease in temperature in the patient after the warmwater sponge technique was applied. Conclusion: SeeThe more attractive the health education media, the more respondents will be interested in knowing the information provided in health education, so that health education becomes more effective